On Some Relationships of Certain K−Uniformly Analytic Functions Associated with Mittag-Leffler Function - Adel A. Attiya; Ekram E. Ali; Taher S. Hassan; Abeer M. Albalahi (Journal of Function Spaces)
In this paper, we introduce and investigate several inclusion relationships of new k-uniformly classes of analytic functions defined by the Mittag-Leffler function. Also, integral-preserving properties of these classes associated with the certain integral operator are also obtained.